Black Consciousness and Black Theology: Di ya thoteng di bapile (relationship for liberation) - Resane, Kelebogile T. (HTS teologiese studies, 2024)
The aim of this article is to point out that Black Consciousness and Black Theology are conceptually and philosophically comrades in arms, fighting side-by-side for the liberation of the oppressed masses, especially the black people emerging from apartheid South Africa. Through the literature review, the two philosophical disciplines are historically sketched, defined, and compared. The Setswana idiom, Di ya thoteng di bapile (comradeship), like many African proverbs and idioms, is philosophically employed as a way of decolonising theology. The idiom is used to demonstrate the symbiotic relationship between Black Consciousness and Black Theology in fighting against structural injustices in societies. Historical evolvement of the two disciplines is narratively presented to demonstrate how the two philosophies can continue to fight together towards the liberation of the marginalised masses in post-apartheid South Africa. The article concludes by sketching some strategic initiatives that can be undertaken to create the space for these two disciplines to symbiotically lead to the liberation of people living under the new form of political, cultural and socio-economic marginalisations. The strategic initiatives include the enhancement of self-reliance, prophetic role, and dialogical processes that lead to emancipation of those who sense self-pity, dependency syndrome, and loss of sense of quality life. These initiatives can be achieved through symbiotic cooperation of Black Consciousness and Black Theology, eventually leading to human liberation from any form of oppression.Contribution: There is a symbiotic cooperation of Black Consciousness and Black Theology, eventually leading to human liberation from any form of oppression.